SACRALISATION MARKETING STRATEGY (INNOVATIVE BRANDING FOR INDONESIAN LOCAL CULTURE) - Donny Susilo (BISE: Jurnal Pendidikan Bisnis dan Ekonomi, 2018)
The integrated program on poverty reduction proposed by Indonesian government, though statically proven reduce the poverty rate Indonesia, still invite critiques from experts argued that it was not really effective and touched root of problems. Therefore new approach has to be introduced. This paper introduced new brand strategy for local culture that can empower local people to survive by their own and by this way. The distribution of government program shall not be issue anymore. Theory of cultural branding was used as fundamental of this paper. Bali island has been successfully applied this strategy since a long time ago. It is interesting fact that tourists had got much education about the sacred culture and traditional belief in products and places in Bali. Therefore they were motivated to consume, some of them looked for safety, happiness, miracle and benefit from sacred story. This strategy is proven effective since it can increase price of their product beyond logic and it is potential to apply widely in other areas such as Batu, Singapore and other cultural areas both in Indonesia and in global scope.